2022
DOI: 10.21037/qims-21-659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 320-row CT reconstruction technology on fractional flow reserve derived from coronary CT angiography based on machine learning: single- versus multiple-cardiac periodic images

Abstract: Background: Fractional flow reserve derived from computed tomography (CT-FFR) can be used to noninvasively evaluate the functions of coronary arteries and has been widely welcomed in the field of cardiovascular research. However, whether different image reconstruction schemes have an effect on CT-FFR analysis through single-and multiple-cardiac periodic images in the same patient has not been investigated.Methods: This study retrospectively enrolled 122 patients who underwent 320-row computed tomography (CT) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that the CACS can be used as a proxy for coronary atherosclerotic plaque burden to predict cardiovascular risk [ 45 ], and the CACS increases with cardiovascular risk in the T2DM patient population [ 46 ] to serve as a composite measure of atherosclerotic disease [ 16 ]. CT-FFR, as an indicator of coronary vascular haemodynamic stenosis, provides both physiological and corresponding anatomical information about the coronary vessels [ 47 ]; DS directly reflects the anatomical stenosis of the coronary vessels. Whereas PAT is located near the myocardium, and its excessive activity accelerates coronary atherosclerosis and, thus, cardiovascular disease [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the CACS can be used as a proxy for coronary atherosclerotic plaque burden to predict cardiovascular risk [ 45 ], and the CACS increases with cardiovascular risk in the T2DM patient population [ 46 ] to serve as a composite measure of atherosclerotic disease [ 16 ]. CT-FFR, as an indicator of coronary vascular haemodynamic stenosis, provides both physiological and corresponding anatomical information about the coronary vessels [ 47 ]; DS directly reflects the anatomical stenosis of the coronary vessels. Whereas PAT is located near the myocardium, and its excessive activity accelerates coronary atherosclerosis and, thus, cardiovascular disease [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through this process, the author found that the highest accuracy was achieved with a learning rate of 0.00001, a dropout rate of 0.3, and the Adam optimizer. Furthermore, the DenseNet model exhibited the highest accuracy, precision, recall, and F1-Score (93%) compared to the other pretrained models, ResNet-50 and VGG-16 [22].…”
Section: Literature Reviewmentioning
confidence: 94%
“…Coronary artery disease (CAD) is one of the diseases with the highest morbidity in the world ( 1 ), and despite current improvements in interventional and pharmacological treatments, acute coronary syndrome (ACS) remains a leading cause of death in developed countries ( 2 ). Inflammation of coronary vessels will ultimately promote atherosclerosis and atherothrombosis in patients with ACS ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%